Cardiac adaptation to exercise in adolescent athletes of African ethnicity: an emergent elite athletic population. Issue 9 (31st January 2013) - Sheikh, Nabeel; Papadakis, Michael; Carre, Francois; Kervio, Gaelle; Panoulas, Vasilis F; Ghani, Saqib; Zaidi, Abbas; Gati, Sabiha; Rawlins, John; Wilson, Mathew G; Sharma, Sanjay
Abstract : Background/aims: Adult black athletes (BA) exhibit left ventricular hypertrophy (LVH) on echocardiography and marked ECG repolarisation changes resembling those observed in hypertrophic cardiomyopathy (HCM). Limited data are available for adolescent BA, the group most vulnerable to exercise-related sudden cardiac death. Methods: Between 1996 and 2011, 245 male and 84 female adolescent BA from a wide variety of sporting disciplines underwent cardiac evaluation including ECG and echocardiography. Athletes exhibiting T-wave inversions and/or echocardiographic LVH were investigated further for quiescent cardiomyopathies. Results were compared with 903 adolescent white athletes (WA) and 134 adolescent sedentary black controls (BC). Results: LVH on echocardiography was present in 7% of BA compared to only 0.6% of WA and none of the BC. In the very young (<16 years), 5.5% of BA, but none of the WA, demonstrated LVH. Within the BA group, LVH was more prevalent in men compared to women (9% vs 1.2%, p=0.012). T-wave inversions were present in 22.8% BA, 4.5% WA and 13.4% BC. T-wave inversions in BA occurred with similar frequency in men and women and were predominantly confined to leads V1–V4. T-wave inversions in the lateral leads, commonly associated with cardiomyopathies, were present in 2.4% of BA. On a further evaluation and mean follow-up of 8.3 years, none of the athletes exhibited HCM. Conclusions: Athletic training has a pronounced effect on adolescent BA. Black athletes as young as 14 years of age may exhibit left ventricular wall thicknesses of 15 mm and marked repolarisation changes resembling HCM. Male and female BA demonstrate a high prevalence of T-wave inversions.